SANTRI HONESTY CRISIS: TEACERS' EFFORT TO FORM STUDENTS' SIDDIQ CHARACTER THROUGH SANTRI TRIOGY CHARACTER EDUCATION (HUSNUL ADAB) AND GOOD CHARACTER HABITS (PKB) - Hidayah, Putri Isnaini; Aisyah, Nur (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
The crisis of honesty and bad morals of students also destroys students' character. Traditional education known as Islamic boarding school is very important to increase the nation's intelligence and independence. After considering existing problems, there are new innovations that differentiate character formation in formal institutions from Islamic boarding schools. The Teacher's Efforts to Shape the Siddiq Character of Students Through the Santri Trilogy Character Education (Husnul Adab) and the Good Character Practice (PKB) by restoring divine values to humans are actualized by character formation through the santri trilogy which is conceptualized in the culture of santri life. From the results obtained, the Teacher's Efforts in Shaping the Siddiq Character of Madrasah Students Through the Santri Trilogy Character Education (Husnul Adab) and Good Character Habits (PKB) can be seen in: 1) the daily activities of the students in the form of congregational prayers, the implementation of early and formal schools, greeting activities every morning, there are Islamic boarding school regulations, the santri's ta'dzim attitude towards kyai and asatidz. This activity contains the values of the trilogy and the habituation of the good character of the students. 2) The habituation of the good character of the students which is carried out every day at the Islamic boarding school is worthy of being emulated.